Digital back-feeding and the mental health of rural older adults: mediation of basic psychological need satisfaction - Yang, Qijiao; Li, Haomiao; Bi, Shengxian; Chen, Yingchun (Frontiers in Psychology, 2025)
BackgroundThis study aims to explore the mediating role of basic psychological need satisfaction in the relationship between digital back-feeding and mental health (specifically depression and loneliness) in rural older adults. The objective is to examine how different forms of digital back-feeding influence mental health by enhancing the satisfaction of basic psychological needs.MethodsThis study employed a multistage stratified sampling method, in which 1,663 valid survey responses were collected online. Depression and loneliness in older adults were measured using the Center for Epidemiologic Studies-Depression Scale and UCLA Loneliness Scale-6, respectively. Sociodemographic characteristics were controlled for in the analysis.ResultsDigital access, skills, and literacy were identified as significant negative predictors of depression and loneliness among older adults in rural areas, with basic psychological need satisfaction serving as a key mediator in this relationship. The adverse effects of digital access on depression and loneliness were especially pronounced among men, residents of lower-GDP regions, and individuals from low-income groups.ConclusionThis study explored the impact of digital back-feeding on the psychological health of older adults in rural areas, with a focus on the mediating role of basic psychological need satisfaction. The results revealed considerable heterogeneity in the effects of digital back-feeding on mental health, with variations across gender, regional economic development, and income levels. Based on these findings, we recommend that policymakers promoting digital empowerment consider these factors to design more targeted and effective intervention strategies.